The present and future of geriatric internal medicine: a bibliometric analysis - Chen, Yingjie; Dong, Xiuli; Jia, Yan (Frontiers in Medicine, 2025)
With the gradual progress of global aging, geriatric medicine is becoming increasingly popular, and within geriatric medicine, internal medicine holds a very important position. Understanding the situation in the field of geriatric internal medicine helps researchers gain a comprehensive understanding of this area. In this study, we analyzed and visualized relevant literature from the Web of Science Core Collection database using bibliometric methods, collecting a total of 831 articles, with a time span from 1978 to August 2024. We analyzed the overview of the field, the degree of aging and the volume of publications by country, the core journals in the field, the collaboration relationships among institutions and authors, as well as the hotspots and their changes, and discussed the results. This study provides a broad perspective for professionals in the field of geriatric internal medicine and discusses the future research development in the field.